The methodological quality of health economic evaluations for the management of hip fractures: A systematic review of the literature - Sabharwal,S; Carter,A; Darzi,LA; Reilly,P; Gupte,CM (SURGEON-JOURNAL OF THE ROYAL COLLEGES OF SURGEONS OF EDINBURGH AND IRELAND, 2015)
Background and objectivesApproximately 76,000 people a year sustain a hip fracture in the UK and the estimated cost to the NHS is £1.4 billion a year. Health economic evaluations (HEEs) are one of the methods employed by decision makers to deliver healthcare policy supported by clinical and economic evidence. The objective of this study was to (1) identify and characterize HEEs for the management of patients with hip fractures, and (2) examine their methodological quality.MethodsA literature search was performed in MEDLINE, EMBASE and the NHS Economic Evaluation Database. Studies that met the specified definition for a HEE and evaluated hip fracture management were included. Methodological quality was assessed using the Consensus on Health Economic Criteria (CHEC).ResultsTwenty-seven publications met the inclusion criteria of this study and were included in our descriptive and methodological analysis. Domains of methodology that performed poorly included use of an appropriate time horizon (66.7% of studies), incremental analysis of costs and outcomes (63%), future discounting (44.4%), sensitivity analysis (40.7%), declaration of conflicts of interest (37%) and discussion of ethical considerations (29.6%).ConclusionsHEEs for patients with hip fractures are increasing in publication in recent years. Most of these studies fail to adopt a societal perspective and key aspects of their methodology are poor. The development of future HEEs in this field must adhere to established principles of methodology, so that better quality research can be used to inform health policy on the management of patients with a hip fracture.